Meeting the social needs of geriatric hospital patients - Benek, Iwona Dorota; Szewczenko, Anna Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article presents the functional factors of geriatric hospitals and their influence on the fulfillment of the patients’ social needs. It has been assumed that there exist a number of spatial determinants that may become important elements supporting the activity of the elderly staying in geriatric hospitals. As a result qualitative research has been performed on selected Polish and foreign examples in order to indicate recommended solutions connected with the location, the shaping of the building itself as well as selected functional zones used by the patients. Social needs of elderly patients have been discussed which is the basis for assuming specific design solutions.